Comparison of Group Decision Making in Japan, Thailand, Vietnam, and Russia Using a Business Game. (December 2017) - Morita, Mitsuru; Iwai, Chiaki; Rompho, Nopadol; Phadoongsitthi, Monvika
Background. Numerous preceding research studies have analyzed the relationship betweenstrategy andculture through questionnaires and case studies. However, very few regard the input results of a business game's decision making variables as strategy. Moreover, few conduct an analysis using the same scenario, under a controlled environment from the perspective of experimental business management studies, while using adult subjects with similar characteristics. Aim. This study compared thegroup decision making ofJapan, Thailand, Vietnam, andRussia, particularly analyzing each culture's influence on strategy. We verified the relationship between thecultural dimensions used in the GLOBE project andstrategies within thebusiness game . Method. This was a mixed methods study on the relation betweencultural dimensions andbusiness game entrystrategies, based upon data collected by observation using a quasi-experimental approach that includes questionnaires andbusiness games, and utterance analysis by counting the frequency of words. Findings. Countries differ in their tendencies to engage in sharing, with an emphasis on strategies such as, product differentiation differentiation, being marketing emphasized, or cost saving. Further, we could confirm relationships between severalcultural dimensions andstrategy .